USTP-Panaon Lost and Found Management System - Lasagas, Kenralp P; Daig, Charles S; Pabatang, Ivy Joy M; Sumaylo, Jophet M; Caw-it, Jelly Grace A (MDP Student Conference, 2025)
The USTP-Panaon Lost and Found Management System leverages QR code technology and a mobile/web application to modernize item retrieval processes within an academic setting. This project addresses inefficiencies in traditional lost-and-found methods, such as manual records and disorganized retrieval systems. A centralized database ensures efficient item management, while QR codes facilitate quick identification and tracking. The system fosters seamless communication between finders and owners, enhancing user experience and operational efficiency. Evaluation results indicate the system's success across key metrics, including functionality, reliability, usability, efficiency, and security, rated as “Very Good” by users and administrators. While the system demonstrates high adoption potential, challenges such as network dependency and user engagement were noted. Aligned with sustainable development goals, the system promotes responsible resource use and technological innovation in education. By transforming traditional administrative tasks into streamlined digital processes, this initiative enhances campus organization and stakeholder satisfaction. Recommendations for future development include improved notification mechanisms, reporting features, and an administrator announcement panel to further enhance usability and communication.